Growth differentiation factor 8 regulates SMAD2/3 signaling and improves oocyte quality during porcine oocyte maturation in vitro†. Issue 1 (20th April 2019) - Yoon, Junchul David; Hwang, Seon-Ung; Kim, Mirae; Jeon, Yubyeol; Hyun, Sang-Hwan
Abstract: Growth differentiation factor 8 (GDF8), also known as myostatin, is a member of the transforming growth factor-β (TGF-β) family and has been identified as a strong physiological regulator of muscle differentiation. Recently, the functional role of GDF8 in reproductive organs has received increased interest following its detection in the human placenta and uterus. To investigate the effects of GDF8 during porcine oocyte in vitro maturation (IVM), we assessed the quality of matured oocytes. Furthermore, we investigated the specific gene transcription and protein activation levels in oocytes and cumulus cells after IVM and subsequent embryonic development after in vitro fertilization and parthenogenetic activation. Prior to these experiments, the concentration of GDF8 in porcine follicular fluid was determined. During the entire IVM period, 1.3 ng/mL GDF8 and its signaling inhibitor SB431542 (SB) at 5 μM were added as control, SB, SB + GDF8, and GDF8 groups, respectively. Our results demonstrate that supplementation with GDF8 during porcine oocyte IVM enhanced both meiotic and cytoplasmic maturation, with altered transcriptional patterns, via activation of Sma- and Mad-related protein 2/3 (SMAD2/3). Using the pharmacological inhibitor SB431542, we demonstrated that inhibition of GDF8-induced Smad2/3 signaling reduces matured oocyte quality. In conclusion, for the first time, we demonstrated paracrine factor GDF8 in porcine follicular fluid in vivo. Furthermore, we showed that GDF8 supplementation improved mature oocyte quality by regulating p38 mitogen-activated protein kinase phosphorylation and intracellular glutathione and reactive oxygen species levels during porcine IVM. Abstract : The supplementation of GDF8 which present in porcine follicular fluid regulates p38 MAPK phosphorylation and intracellular GSH and ROS levels during immature oocyte maturation in vitro.